2017
DOI: 10.5194/se-8-1119-2017
|View full text |Cite
|
Sign up to set email alerts
|

Land-use changes influence soil bacterial communities in a meadow grassland in Northeast China

Abstract: Abstract. The conversion of natural grassland into agricultural fields is an intensive anthropogenic perturbation commonly occurring in semiarid regions, and this perturbation strongly affects soil microbiota. In this study, the influences of land-use conversion on the soil properties and bacterial communities in the Horqin Grasslands in Northeast China were assessed. This study aimed to investigate (1) how the abundances of soil bacteria changed across land-use types, (2) how the structure of the soil bacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 61 publications
1
16
2
Order By: Relevance
“…RDA ordination indicated that soil SOC content, pH, and AP played dominant roles in shaping the microbial community composition (Figure 4). This observation was contradictory to previous findings that pH was the key factor regulating the structures of bacterial community in soils (Cao et al, 2017), both on large and fine scales (Shen et al, 2013). Meanwhile, it has been shown that SOC was the best predictor for microbial community structure in soils across different agricultural land management at a given location (Sul et al, 2013).…”
Section: Linking Soil Characteristics With Keystone Taxa In Soilscontrasting
confidence: 85%
“…RDA ordination indicated that soil SOC content, pH, and AP played dominant roles in shaping the microbial community composition (Figure 4). This observation was contradictory to previous findings that pH was the key factor regulating the structures of bacterial community in soils (Cao et al, 2017), both on large and fine scales (Shen et al, 2013). Meanwhile, it has been shown that SOC was the best predictor for microbial community structure in soils across different agricultural land management at a given location (Sul et al, 2013).…”
Section: Linking Soil Characteristics With Keystone Taxa In Soilscontrasting
confidence: 85%
“…Intensive anthropogenic perturbations like the transformation of natural lands into managed lands have been reported to intensely alter soil microbiota. Approximately 40% of lands worldwide have been transformed into controlled systems and about 85% of them are affected by anthropogenic activities in one way or the other [13][14][15]. Humans have increased the immensity of land-use and land-use change is the most direct indication of the influences of human actions on the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use conversion strongly alters natural ecosystems, often leading to habitat destruction (Cao et al 2017). In Poland, the National Programme for Increasing Forest Cover has been introduced, with the aim of increasing forest cover from 29.4% (present level) to 30% by 2020 (Report on the State of Forests in Poland 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many soils are used improperly, which leads to their degradation. The assessment of soil quality is crucial in monitoring ecosystem stability and the sustainability of ecosystem services (Saviozzi et al 2001;Cao et al 2017).…”
Section: Introductionmentioning
confidence: 99%